MUAMMOLI KREDITLARNI SUDGACHA VA SUD JARAYONIDA UNDIRISH MEXANIZMLARINI TAKOMILLASHTIRISH (Marketing Journal, 2026)
AbstractThis article highlights the existing mechanisms for recovering problem loans inpre-trial and judicial proceedings, as well as opportunities for their improvement.During the study, the main problems encountered in the recovery of problem loanswere analyzed, and existing legal norms, banking practice, and execution processeswere studied. Also, relevant approaches and proposals and recommendations have beenformed to improve the efficiency of working with debtors at the pre-trial stage, and tosimplify and accelerate the collection mechanisms in the judicial process.Keywords: problematic loan, loan in litigation, overdue debt, diversification, risk.